STRATEGI PENINGKATAN PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) WISATA PANTAI BATU KUMBANG KABUPATEN MUKOMUKO PERSPEKTIF INDUSTRI HALAL - Siti Khodijah; Desi Isnaini; Khozin Zaki (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the income conditions of Micro, Small, and Medium Enterprises (MSMEs), the implementation of the halal industry concept, and strategies to increase MSME income in the Batu Kumbang Beach tourism area, Mukomuko Regency. The research employed a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation involving MSME owners operating in the tourism area. The findings reveal that MSME income is influenced by several factors, including the number of tourist visits, business location, types of products or services offered, and the quality of customer service. The implementation of the halal industry concept is reflected in the use of halal raw materials, business cleanliness, friendly services, and a tourism environment that aligns with Islamic values. However, most MSME operators have not yet obtained official halal certification. Strategies to increase income include improving product and service quality, intensifying tourism promotion, maintaining environmental cleanliness, and encouraging halal certification ownership. The existence of Batu Kumbang Beach tourism has contributed positively to increasing MSME income and supporting the economic development of the surrounding community.